2004
DOI: 10.1038/sj.bjc.6601460
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal large B-cell lymphoma (PMLBCL): long-term results from a retrospective multicentre Italian experience in 138 patients treated with CHOP or MACOP-B/VACOP-B

Abstract: The optimal treatment of primary mediastinal large B-cell lymphoma (PMLBCL) is still undefined. In the absence of randomised studies, we retrospectively analysed:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 31 publications
11
154
1
4
Order By: Relevance
“…A similar comparison of 138 patients from 13 Italian institutions favored MACOP-B or VACOP-B over CHOP. 44 Eighty percent of the former patients entered a CR compared to 51% with CHOP (P < .001); significantly fewer patients failed to demonstrate a response or progressed on therapy (9% vs 42%; P < .01). Both event-free and OS were superior in the MACOP-B/ VACOP-B group.…”
Section: Is a Third Generation Chemotherapy Regimen Needed For Pmbl?mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar comparison of 138 patients from 13 Italian institutions favored MACOP-B or VACOP-B over CHOP. 44 Eighty percent of the former patients entered a CR compared to 51% with CHOP (P < .001); significantly fewer patients failed to demonstrate a response or progressed on therapy (9% vs 42%; P < .01). Both event-free and OS were superior in the MACOP-B/ VACOP-B group.…”
Section: Is a Third Generation Chemotherapy Regimen Needed For Pmbl?mentioning
confidence: 99%
“…This reflected in the observation that 50% of patients have low IPI scores at presentation. 42 The age-adjusted IPI has generally been reported to be of limited predictive value, [43][44][45] although in a recent series of 92 patients there was some clear discriminative value. 46 Elevation of LDH to greater than twice the upper limit of normal, age over 40 and performance status ≥ 2 all correlated with reduced survival in a population-based series from British Columbia, 43 while in a large series from the International Extranodal Lymphoma Study Group (IELSG) male sex, poor performance status and advancedstage disease were significant negative predictors of survival.…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several studies described lower survival rates for PMBCL with bulky masses after standard treatment [4][5][6], as compared with other DLCLs, suggesting the need for more intensive chemotherapy. As a matter of fact, the efficacy of third-generation regimens, such as MACOP-B (methotrexate, doxorubicin, cyclophosphamide, vincristine, prednisone, and bleomycin), has been reported with a CR rate as high as 89%.…”
Section: Discussionmentioning
confidence: 99%
“…The aggressive clinical behavior and the patients' age require intensive treatment, and retrospective studies have reported the efficacy of third-generation regimens plus radiotherapy (RT) as compared to classical CHOP [4][5][6].…”
Section: Introductionmentioning
confidence: 99%